2006
DOI: 10.1381/096089206776327314
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Gastric Re-Banding versus Laparoscopic Gastric Bypass as a Rescue Operation for Patients with Pouch dilatation

Abstract: Conversion to LRYGBP appears to offer significant advantages, and appears to be the rescue therapy of choice after failed laparoscopic gastric banding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 19 publications
1
20
0
2
Order By: Relevance
“…Furthermore, complication rates are similar to rebanding rates [11,14,17,[20][21][22]24]. When revisional surgery is performed by experienced hands, creation of an LRYGB after failed AGB can have similar complication rates as primary LRYGB surgery [8,14,17,19,21,24,25]. The recent 21:1931-1935 1933 series by Spivak, in which 33 patients underwent a conversion of band to gastric bypass, confirmed the results of previous series without mortality, with two severe complications (one splenectomy and one internal hernia), which can be considered a technical error [29].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Furthermore, complication rates are similar to rebanding rates [11,14,17,[20][21][22]24]. When revisional surgery is performed by experienced hands, creation of an LRYGB after failed AGB can have similar complication rates as primary LRYGB surgery [8,14,17,19,21,24,25]. The recent 21:1931-1935 1933 series by Spivak, in which 33 patients underwent a conversion of band to gastric bypass, confirmed the results of previous series without mortality, with two severe complications (one splenectomy and one internal hernia), which can be considered a technical error [29].…”
Section: Discussionmentioning
confidence: 68%
“…Nonetheless, in the setting of inadequate weight loss after band placement, RYGB appears to be a superior procedure [8,14,17,19,21,24,25]. Of four studies analyzing the results after rebanding only one reported postoperative BMI, and it was unchanged after 12 months [11,14,20,22].…”
Section: Discussionmentioning
confidence: 99%
“…Even procedures acceptable by current standards, such as VBG [215], RGB [216], and AGB, are at risk for Lap laparoscopic, AGB adjustable gastric banding, RGB Roux-en-Y gastric bypass, BPD biliopancreatic diversion Guidelines for laparoscopic AGB • The pars flaccida approach for laparoscopic AGB placement should be used instead of the perigastric approach to decrease the incidence of gastric prolapse (level 2) • Laparoscopic AGB is effective in all BMI subgroups, with durable weight loss and control of comorbidities past 5 years (level 1) • Intermediate-term weight loss after laparoscopic AGB may be less than after laparoscopic RGB (level 1) • Frequent outpatient visits are suggested in the early postoperative period. Band filling should be guided by weight loss, satiety, and patient symptoms (level 3) anatomic derangement that may be amenable to surgical revision [217][218][219]. In recent years, the explosion of bariatric surgery also has resulted in application of interventions that may create unfamiliar anatomy and complications for surgeons performing revisional procedures [220].…”
Section: Anatomic Failurementioning
confidence: 99%
“…However, BPD, AGB, and other operations also have been used in this setting [231][232][233]. Likewise, most authors advocate RGB for revision of AGB because of complications or insufficient weight loss [217][218][219], although other operations have been applied [234,235]. Finally, in cases of failed BPD ?…”
Section: Anatomic Failurementioning
confidence: 99%
“…A number of pure restrictive procedures that involved gastric partitioning with staples have been limited by stomal dilation or recanalization of nondivided staple lines [213,214]. Even procedures acceptable by today's standards, such as VBG [215], RGB [216], and AGB are at risk for anatomic derangement that may be amenable to surgical revision [217,218,219]. In recent years, the explosion of bariatric surgery has also resulted in application of interventions that may create unfamiliar anatomy and complications for surgeons performing revisional procedures [220].…”
Section: Anatomic Failurementioning
confidence: 99%